Pengaruh Trust dan Communication Terhadap Customer Loyalty di Perbankan (Studi Kasus pada nasabah Bank Mandiri Cabang Soekarno Hatta di Malang) - Febrina Mayang Sari (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of  the study  to determine  the variables of trust and  communication  in partial effect on customer loyalty customer Soekarno Hatta bank branch  in Malang, and  to determine the  trust  and  communication  variables  jointly  influence on  customer loyalty customer Soekarno Hatta bank branch in Malang.  The population used in this study is a customer of the bank branch in Malang Soekarno Hatta with the characteristics of men and women, residing in Malang, at least high school education or its equivalent for the reason the customer has the ability to understand the questions on the questionnaire, the minimum has been customer savings bank during the past 2 years. The number of samples used is 130 respondent.  The research proves that trust (X1) and Communication (X2) simultaneously significant effect on customer loyalty variables. means higher customer confidence and better communication that exists only between the bank and its customers, the higher will affect customer loyalty to  Bank Mandiri. The research proves that trust and communication are partially significant effect on customer loyalty variables. Keywords:  Trust,  Communication, Customer Loyalty